2020
DOI: 10.1021/acs.est.0c02175
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-Suppressed Selenite Biotransformation by Escherichia coli

Abstract: Biotransformation of selenite to valuable elemental selenium nanoparticles (Se0) is a promising avenue to remediate seleniferous environments and simultaneously recover selenium (Se). However, the underlying oxyanion competition and selenite transformation mechanism in prokaryotes are poorly understood. In this work, the impacts of phosphate on selenite uptake and transformation were elucidated with Escherichia coli and its mutant deficient in phosphate transport as model microbial strains. Selenite uptake was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Janine: Considering the various reports about selenite transporters we already mentioned, I’m tempted to conclude that tellurite and selenite should be transported by the same carriers, contrary to what is believed, and that many different transporters are involved in the transport of these oxyanions. In a recent work with E. coli [ 92 ], for example, it is reported that in cultures amended with 0.1 mM selenite, addition of increasing phosphate concentration up to 30 mM, progressively decreased the incorporation of Se in the biomass, thus indicating that phosphate ions prevented selenite uptake. It must be noted, however, that none of the phosphate concentrations tested, completely suppressed selenite uptake (see also Table 1 ).…”
Section: How Does Selenite And/or Tellurite Enter Bacterial Cells?mentioning
confidence: 99%
See 2 more Smart Citations
“…Janine: Considering the various reports about selenite transporters we already mentioned, I’m tempted to conclude that tellurite and selenite should be transported by the same carriers, contrary to what is believed, and that many different transporters are involved in the transport of these oxyanions. In a recent work with E. coli [ 92 ], for example, it is reported that in cultures amended with 0.1 mM selenite, addition of increasing phosphate concentration up to 30 mM, progressively decreased the incorporation of Se in the biomass, thus indicating that phosphate ions prevented selenite uptake. It must be noted, however, that none of the phosphate concentrations tested, completely suppressed selenite uptake (see also Table 1 ).…”
Section: How Does Selenite And/or Tellurite Enter Bacterial Cells?mentioning
confidence: 99%
“…Davide: Janine, let me remind you that the latter competition experiments you mentioned [ 92 ], were carried out under experimental conditions very far from the expected 1 to 1 ratio between two reactants that should compete specifically for a common carrier, as vice versa we observed between tellurite and acetate in R. capsulatus [ 64 , 65 ].…”
Section: How Does Selenite And/or Tellurite Enter Bacterial Cells?mentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that SeNPs were less bioavailable than SeO 3 2– . It has been reported that SeO 3 2– can be easily transported across the membrane via binding to the sulfhydryl sites on the cell membrane or by phosphate transfer protein ( Yu et al, 2018 ; Zhu et al, 2020 ). In contrast, SeNPs are in a reduced state.…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli , Na 2 SeO 3 uptake is inhibited by phosphate, and intracellular Se is transformed from Se 0 to organoselenium compounds when the phosphate level is high. This is mainly attributed to the competitive uptake of phosphate and Na 2 SeO 3 mediated by the low-affinity phosphate transporter PitA [ 16 ].…”
Section: How To Synthesize Designer Nanocrystals In Live Cellsmentioning
confidence: 99%